The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/1806513
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 Expression in Patients with Abdominal Aortic Aneurysm and Its Role in the Necroptosis of Vascular Smooth Muscle Cells

Abstract: Background. Our previous studies have shown that interleukin- (IL-) 37 plays a protective role in patients and animal models with coronary artery disease. However, the role of IL-37 in patients with abdominal aortic aneurysm (AAA), another artery disease, is yet to be elucidated. Methods and Results. AAA tissues and plasma samples were obtained from patients with or without surgical intervention. Normal renal aortic tissues were collected from kidney transplant donors. Our findings established that in AAA, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This is one of the limitations to the current study. Previous studies have confirmed that IL-37 is a potential inhibitor of P65 and may exert anti-inflammatory effects by inhibiting the phosphorylation and nuclear translocation of P65 (39)(40)(41). P65 activation has also been suggested as a key mechanism for increased inflammation levels in diabetic atherosclerotic mice (42,43).…”
Section: Discussionmentioning
confidence: 91%
“…This is one of the limitations to the current study. Previous studies have confirmed that IL-37 is a potential inhibitor of P65 and may exert anti-inflammatory effects by inhibiting the phosphorylation and nuclear translocation of P65 (39)(40)(41). P65 activation has also been suggested as a key mechanism for increased inflammation levels in diabetic atherosclerotic mice (42,43).…”
Section: Discussionmentioning
confidence: 91%
“…The levels of IL-10 and TGF-b secreted by T cells isolated from patients were decreased in the treatment of rhIL-37 (91). Although the role of IL-37 in the animal model and clinical patients with atherosclerosis (93)(94)(95)(96), acute coronary syndrome (1,97), coronary artery calcification (98), coronary heart disease (99), chronic heart failure (100), atrial fibrillation (101), abdominal aortic aneurysm (102), hypertension (103), and other cardiovascular system diseases (91) has been identified, the timeline view of cocitation clusters revealed that the relationships between IL-37 and the cardiovascular system diseases remain the future hotspots. Cluster #0 seems to be the transfer of the second part of cluster #1 which has been undertaken in terms of research content.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed lineage kinase domain-like pseudokinase (MLKL) and calcium/calmodulin-dependent protein kinase II (CaMKII) are downstream effectors of RIP1-dependent necroptosis in AAA. Interestingly, pharmacological inhibition of necroptosis by targeting RIP1 or RIP3 ameliorates aneurysm expansion and even stabilises pre-existing aneurysms attenuating inflammation and inducing ECM repair [203,204], while, recently, the protective role of IL-37 on aneurysmal disease has been related to its ability to suppress RIP3-mediated necroptosis [205]. These findings have encouraged active research aiming at characterising the regulatory mechanisms underlying RIP3 upregulation in AAA [206], which will provide grounds for new therapeutic strategies for this disease.…”
Section: Loss Of Vsmc By Necroptosismentioning
confidence: 99%